The incidence of difficult intubation in 2 000 patients undergoing thyroid surgery: A single center experience - Kalezić Nevena; Milosavljević Radoje; Paunović Ivan; Živaljević Vladan; Diklić Aleksandar; Matić Danica; Ivanović Branislava; Nešković Vojislava (Vojnosanitetski Pregled)
Background/Aim. The incidence of difficult intubation (DI) is 1-10%, and DI leading to inability to intubate occurs in 0.04% of the population. The aim of this study was to evaluate the incidence of DI in thyroid surgery and to assess possible correlation of difficult tracheal intubation with sex and primary diagnosis. Methods. We studied 2 000 consecutive patients (1 705 females) scheduled for thyroid surgery who were assessed for DI prior to general anesthesia, with respect to primary disease diagnosis and sex. Patients were divided into four groups: patients with nodal goiter (group A), polynodal goiter (group B), hyperthyroidism (group C) and thyroid carcinoma (group D). Difficult intubation was predicted using the scoring system which included 13 parameters ranged from 0 to 2. Additive score > 5 was accepted as a predictor of DI. True DI was defined as impossible visualization of glottis with direct laryngoscopy (grade III and IV). Results. Difficult intubation was observed in 110/2 000 patients (5.5%). The incidence of DI was higher in males (26/295, 8.8%) then females (84/1 705, 4.9%) (p < 0.01). The incidence of DI was highest in the group B (6.2%). Extremely DI occurred in 15/2000 patients (0.75%), the most of them in the group C (1.1%). Sensitivity of used scoring system was 91.8% and specificity 86.5%. Conclusions. The incidence of DI was highest in patients with polynodal goiter but extremely DI was present mostly in patients with hyperthiroidism. Men seem to be at higher risk for DI than women. Scoring system used in this study for prediction of DI may be useful in this patient population.